2021
DOI: 10.3389/fpubh.2021.767128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitudes, and Factors Influencing the Selection Student of Generic Medicine

Abstract: Background: Generic replacements for branded medicines have become a typical practice among registered pharmacists all over the world. Therefore, this study was aimed to determine the influence of the knowledge and attitudes of PharmD students and other factors on the selection of unbranded medicines.Methods: A descriptive, cross-sectional study was conducted through Google Forms to collect data using self-reported questionnaires. The data was collected over a period of 3 months, from January to March 2021, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Findings on the key factors for the selection and prescription of generic drugs confirmed those reported previously in a study conducted in Saudi Arabia and included the financial situation of patients, the cost-effectiveness of generic drugs, and the lack of possible alternatives. 30 Furthermore, supportive legislation and regulations were also identified as potential factors for generic drug selection, in agreement with the literature. 33 Despite the negative perception of physicians towards the implementation of the unified medical prescription to increase generic drug prescription in Lebanon, 34 the Ministry of public health adopted a list of substitutable drugs for pharmacists to base their decision on and could be a successful method to lower medical expenses.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Findings on the key factors for the selection and prescription of generic drugs confirmed those reported previously in a study conducted in Saudi Arabia and included the financial situation of patients, the cost-effectiveness of generic drugs, and the lack of possible alternatives. 30 Furthermore, supportive legislation and regulations were also identified as potential factors for generic drug selection, in agreement with the literature. 33 Despite the negative perception of physicians towards the implementation of the unified medical prescription to increase generic drug prescription in Lebanon, 34 the Ministry of public health adopted a list of substitutable drugs for pharmacists to base their decision on and could be a successful method to lower medical expenses.…”
Section: Discussionsupporting
confidence: 75%
“…5 In addition, Most participants agreed that generic medicines must be cheaper than brands, bioequivalent, and were considered therapeutically equivalent to their corresponding brands, which is comparable to previous research in similar settings. 28,30 A significant proportion of Lebanese pharmacists held positive perceptions of generic medicines, disapproving that generics are less effective, less safe, inferior in quality, and more likely to cause side effects compared to brands. These perceptions are in line with some research 30,31 but contradict those from other studies conducted in New Zealand and in Ethiopia, in which pharmacists had safety and quality concerns about generics .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also found that Males have a better attitude about the criteria used in drug formulary selection when compared to their female counterparts. Again, Alarifi [ 27 ] and Bilal et al [ 28 ] report that most healthcare professionals have knowledge and positive attitude toward generic medicine and its selection criteria. Bagga [ 29 ] also reports that pharmacists and doctors are knowledgeable about the use of formulary.…”
Section: Discussionmentioning
confidence: 99%